Sleep apnea as a comorbidity in obese psoriasis patients: a cross‐sectional study. Do psoriasis characteristics and metabolic parameters play a role?. (23rd May 2012) - Papadavid, E.; Vlami, K.; Dalamaga, M.; Giatrakou, S.; Theodoropoulos, K.; Gyftopoulos, S.; Stavrianeas, N.; Papiris, S.; Rigopoulos, D.
Abstract Background Psoriasis is associated with a variety of comorbidities such as obesity and cardiovascular disease. Objective In a cross‐sectional study, we explored whether obstructive sleep apnea and hypopnea syndrome (OSAHS) is associated with psoriasis characteristics and metabolic parameters. Methods Thirty‐five patients with chronic plaque psoriasis underwent a nocturnal polysomnography study and were analysed for Apnoea–Hypopnoea Index to assess OSAHS severity and Framigham score to predict the absolute risk of coronary artery disease at 10 years. The association of OSAHS with psoriasis was examined according to psoriasis characteristics (PASI and DLQI scores, disease duration and previous use of systemic treatments), metabolic parameters (Body Mass Index – BMI, waist to hip ratio – WHR, lipid profile) and other comorbidities (obesity, hypertension, arthritis and cardiovascular disease). Results There was no correlation between psoriasis characteristics and OSAHS. Psoriasis patients with OSAHS presented more frequent snoring and lower sleep quality compared with those without OSAHS. In univariate analyses, OSAHS was associated with increased BMI and hypertension in psoriasis patients. In multivariable logistic regression models, there was statistically significant evidence that only BMI and hypertension were associated with increased risk of OSAHS, adjusting for psoriasis characteristics, age and gender. Presence of metabolic syndrome, WHR, and smoking were not significant risk factors for OSAHS. In subgroup analyses, OSAHS correlated with duration of psoriasis (>8 years) in women (P = 0.021) and with Framigham score in men (P = 0.035). Conclusion OSAHS may be a comorbidity in obese psoriasis patients with hypertension. Treatment with continuous positive airway pressure and weight loss interventions should be initiated.